THE ROLE OF ENTREPRENEURIAL ORIENTATION IN BUILDING THE COMPETITIVE ADVANTAGE OF COFFEE SHOP - Maya Setiawardani; Abdul Malik Sayuti; Tangguh Dwi Pramono (Jurusan Manajemen Fakultas Ekonomi Universitas Sriwijaya, 2023)
The increasing impact of covid-19, especially in the economic sector, has caused the government to impose a new policy called the new normal. This policy is expected to be able to restore business activities, including coffee shop businesses in the Bandung region, Indonesia. It is hoped that this new normal, sooner or later, will re-rotate the wheels of the economy. This current study aims to (1) identify the level of entrepreneurial orientation and competitive advantage of coffee shop business actors in Bandung in this new normal era, and (2) measure the role of entrepreneurial orientation in building competitive advantage. This research employed the quantitative method. The non-probability sampling with a purposive sampling technique was used to collect data from 100 respondents who were asked to fill in a questionnaire containing the Likert scale. The data were then processed by SPSS and analyzed using descriptive analysis, correlation analysis, regression analysis, coefficient determination analysis, and hypothesis testing. The results indicate that the entrepreneurial orientation and competitive advantage of coffee shop business actors in Bandung in this new normal era are at a “high” level, and entrepreneurial orientation has a significant role in building competitive advantage by 51.7%.